Primary processing of mammalian rRNA involves two adjacent cleavages and is not species specific. - Kass, S (1987)
The primary transcript of the mouse rRNA gene is rapidly processed at nucleotide approximately +650 both in vivo and in vitro. Using run-off transcription in a mouse cell extract as well as S1 nuclease and primer extension analysis of cellular RNA, we demonstrated that this primary processing actually results in the formation of two species of downstream RNA which differ in length by approximately 6 nucleotides, indicating the existence of two closely positioned alternative processing sites. The 200-base-pair region just 3' to the mouse processing site has a striking 80% sequence homology with a region of the human rRNA external transcribed spacer, and S1 nuclease analysis of human cellular RNA has demonstrated that an analogous rRNA processing occurs at the 5' border of the homologous human region. Unlike rDNA transcriptional initiation, however, the primary rRNA processing is not highly species specific, for the transcript of a chimeric gene containing the human processing region adjacent to a mouse rDNA promoter was synthesized and correctly processed in a mouse cell extract. This result confirms that mouse and human rRNA undergo a common primary processing event which is evidently directed by sequences within the 200-base-pair conserved sequence region.